Advance in Improving the Electrical Performance of Microbial Fuel Cell. Issue 1 (August 2020) - Wu, Wanjing; Zhang, Duwei; Fang, Ping
Abstract: As a bioelectrochemical hybrid system, microbial fuel cell converts chemical energy into electrical energy through microbial metabolism, which has great advantages of energy conservation and environmental protection, high energy conversion efficiency, and reduced sludge volume. Therefore, how to improve the power generation performance and output power of MFC has been a hot topic in recent years. Based on this, on the basis of reviewing many literatures, this review analyzes the main factors influencing the electrical performance of MFC by combining the principle of MFC and its electronic transfer mechanism, including battery reactor structure, exchange membrane, anode microorganisms, electrode materials and parameters, etc. At the same time, the application prospect of MFC is discussed, including CW-MFC coupling technology, biosensor and sewage treatment technology. Finally, the present challenges of MFC are put forward, and a better application research direction is proposed for the future of MFC.